Reflection on the iron industry in the globalized market - Carvajal, Luis Felipe Camacho (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The main purpose of this essay is to show a new stage of growth and development of steel industry in the World. Acquisitions in the steel sector are the real incentive of changing of commercial flows of China that switchs from a net importer to one of the biggest exporters of this chain. Following the production, commercial flows an apparent consumption of steel in South America let suggest that the region is not demanding what it is produced in there.